Rectus Sheath Hematoma During Pregnancy - A Severe but Easily Overlooked Condition: A Case Report - Yi-Hao Lin; Shing-Tze Hsieh; Hsing-Tse Yu; Tzu-Hao Wang (Elsevier, 2004)
Objective: Rectus sheath hematoma (RSH) of the abdominal wall is a severe condition caused by a tear in the inferior epigastric artery. Due to its relative rarity compared with other obstetric complications, the early recognition of RSH challenges the diagnostic acumen of obstetricians. We report a case of RSH that was initially suspected to be placenta percreta with bleeding into an extrauterine compartment. The differential diagnosis and management of this clinical condition are also discussed. Case Report: A 30-year-old woman, gravida 2 para 1, with a 31-week singleton pregnancy, complained of lower abdominal pain after a week of coughing. Abdominal ultrasonography identified a well-defined, hypoechoic mass with some internal echoes in the right lower quadrant of the abdomen. Doppler sonography detected vascularity with blood flowing around the mass but little within it. The patient underwent cesarean section and exploratory laparotomy because of unstable hemodynamics. After delivery of a 1,680 g male baby, surgical repair of the torn epigastric artery and ruptured rectus abdominis, and sufficient blood transfusion stabilized her condition. Conclusion: RSH should be included in the differential diagnosis of patients with abdominal pain during pregnancy. The key to diagnosis is to suspect that the pain originates from the abdominal wall.